Malware classification through image processing with a convolutional neural network - Marin, David; Orozco Rosas, Ulises; Picos, Kenia (My University, 2022)
This paper presents the implementation of a convolutional neural network employing two different malware datasets. These datasets are converted to images, processed, and resized to 64x64. Through image processing, the convolutional neural network can accurately classify the types of malware families in the datasets. Experimental results to validate the analysis and implementation are provided; they were specifically made to show the proposal’s effectiveness and efficiency. RESUMEN Este documento presenta la implementación de una red neuronal convolucional que emplea dos conjuntos de datos de malware diferentes. Estos conjuntos de datos se convierten en imágenes, se procesan y se redimensionan a 64x64. A través del procesamiento de imágenes, la red neuronal convolucional puede clasificar con precisión los tipos de familias de malware en los conjuntos de datos. Se proporcionan resultados experimentales para validar el análisis y la implementación; se hicieron específicamente para mostrar la eficacia y eficiencia de la propuesta.
SPIE. Digital Library
Proc. SPIE 12225, Optics and Photonics for Information Processing XVI, 122250F
Keywords: Neural network; Malware datasets; Datasets; Campus Tijuana